Marital adjustment and duration of marriage among postgraduate Iranian students in Malaysia - Ghoroghi, Soudabeh; Hassan, Siti Aishah; Baba, Maznah (Canadian Center of Science and Education, 2015)
The current study aimed to examine the relationship between marriage duration and marital adjustment of married Iranian students at postgraduate level in Malaysian universities. To this end, 220 randomly selected married participants completed an online questionnaire via email. The respondents were questioned about their demographic information and completed Locke-Wallace Marital Adjustment Test (LWMAT; Locke & Wallace, 1959). Data analysis provided information about mean scores, frequencies, percentages, and Pearson's correlation. The results disclosed that there was no correlation between length of marriage and marital adjustment and marital adjustment remained fairly stable over time. This study also discusses the popularity of studying in Malaysia among Iranian students at postgraduate levels.